Analysis Of Millennial Preferences Between Life Goals And Career Stability In Private Companies - Sitna Hajar, Elvira; Oktavia, Nila; Kohar, Abdul; Nurhakim, Rahman (CITACONOMIA : Economic and Business Studies, 2024)
This study examines Indonesian millennials' preferences between pursuing life goals and securing career stability in the private sector. Employing a quantitative approach, it surveyed 400 millennials (born 1981-1996) employed across four sectors: finance, technology, manufacturing, and retail. Data were gathered through an online survey using a validated instrument. Results identify three preference patterns: Pure Purpose-Driven (32%), prioritizing meaning over security; Stability-Dominant (42%), favoring job certainty; and Hybrid (26%), balancing both. Logistic regression (Nagelkerke R² = 0.68) indicates financial pressure as the key determinant, with economically burdened millennials 8.2 times more likely to opt for stability. Family collectivism significantly influences decisions, as 68% of respondents cite family expectations. Sectoral variations are notable, with technology showing higher purpose-driven tendencies. The study refines the "Millennial Paradox" by uncovering three concurrent tensions in Indonesian career choices: idealism versus pragmatism, individual autonomy versus familial obligations, and sectoral constraints versus personal aspirations. Practically, it proposes the "Purpose Within Stability" model, integrating work meaning with financial security to enhance human resource strategies in private firms.